Method for treating phosphorus containing wastewater by steel pickling wastewater modified bentonite - LAN WANGRONG; HUANG XUGUANG (2018)
The invention discloses a method for treating phosphorus containing wastewater by steel pickling wastewater modified bentonite. The method comprises the following steps of S1, taking steel pickling wastewater; regulating the proportion of acid and iron ions in the wastewater by waste iron sheets, ferrous sulfate or sulfuric acid; S2, preparing modified bentonite: uniformly mixing the bentonite andregulated pickling wastewater prepared in the step S1; performing magnetic stirring, drying and sieving to prepare the modified bentonite; S3, treating the phosphorus containing wastewater: adding the modified bentonite prepared in the step S2 into inorganic phosphorus containing wastewater; after the pH value is controlled, full stirring is performed; after the complete precipitation, realizingthe treatment on the phosphorus containing wastewater. Polyferric sulfate and acid modified bentonite are combined, so that the adsorptivity on phosphate can be further improved, so that the effect ofusing waste to treat waste